Aging meat at room and cold temperatures on meat quality and aging loss of sheep carcass - Sunarlim, Roswita; Setiyanto, Hadi (Indonesian Journal of Animal and Veterinary Sciences, 2001)
The aim of this research is to compare the quality of meat of local carcass sheep between fresh and aging meat stored at room temperature for 12 hours, at 4oC for one day and one week. For that purpose a study of aging carcass involving 12 local sheep (male and female with different ages) was carried out by separating carcass into two parts: (1) the right portion was aged on 4oC for one day and one week, room temperature for 12 hours, and (2) the left portion as control without aging. A factorial design 2x2 (2 sexes and aging vs without aging) for three kinds of aging on quality of meat. A factorial design 2x3 (2 sexes and 3 kinds of aging) on aging loss. Replicate twice was carried out with different ages (old and young sheep). Parameter measured were pH, warter-holding capacity, cooking loss, color, tenderness, carcass weight loss. There was decrease in pH, increase in tenderness value for aged meat that stored at room temperature for 12 hours (1.84 kg), at cold temperature for one day (2.03 kg), but tenderness value was the most (0.92 kg) at cold temperature for one week compared to fresh meat (3.41, 4.06, and 3.66 kg). Lightness color (l), red color (a) and yellow color (b) for aged meat is usually increase compare to fresh meat, except for aged meat stored at room temperature for 12 hours was decrease significant. Water-holding capacity and cooking loss value of aged meat was not significant compared to fresh meat. Aging loss of aged meat stored at 4oC for one week (13.58%) was significant compared to aged meat stored at room temperature (2.42%) and 4oC for one day (2.90%). Â  Key words: Aging of carcass, room temperature, cold temperature, meat quality, aging loss